Aplikasi Filler Batang Sorgum pada Sintesis Bioplastik dengan Plasticizer Asam Palmitat - Yuli Darni; Dita Synthauli E; Erna Sartika Sinambela; Herti Utami (Universitas Ahmad Dahlan, 2017)
Plastics are used for human use, creating side effects on the environment. The low level of degradation in the plastic makes the environment must accommodate so much plastic waste that causes pollution so that innovation is needed in the manufacture of plastics that can decompose in nature. This study discusses the use of sorghum stalk as a filler in the manufacture of bioplastic. Sorghum starch and chitosan as a bioplastic raw material with a palmitic acid and PEG-400 as a plasticizer. The purpose of this study was determined the effect of sorghum stalk as a filler (packing material) into mechanical properties of bioplastic. Bioplastic produced is expected to resemble a commercial LDPE plastic. Starch-chitosan formulations used in this study was 63 : 35 (w/w), the size of the starch and chitosan was 63 micron sieve, stirring time about 35 minutes and stirring velocity about 375 rpm this research was also conducted various concentration of plasticizer (10,15, 23, 27, 33, 35 wt%). Some analysis of the mechanical test (tensile strength, percent elongation, and modulus young), water resistance, density and FTIR has determined the characteristics of bioplastic. The best result in this research is bioplastic with 1 gr filler formulation at 10% plasticizer concentration with modulus young value characteristic aboutÂ 126,145 MPa, the tensile strength of 7,028 MPa, extension percent about 5,517 %, density about 0,9 gr/mL, the water absorption of 38,88%. The bioplastic characteristic already meet the LDPE plastic standard.